2020
DOI: 10.1177/0967391120929079
|View full text |Cite
|
Sign up to set email alerts
|

Polythiophene/graphene/zinc tungstate nanocomposite: Synthesis, characterization, DC electrical conductivity and cigarette smoke sensing application

Abstract: Herein, we are reporting the synthesis and characterization of polythiophene (PTh) and its novel nanocomposites with zinc tungstate (ZT) and graphene/zinc tungstate (G/ZT) hybrid for Direct current (DC) electrical conductivity based cigarette smoke sensing at room temperature. X-ray diffraction, Fourier-transform infrared, Raman, scanning electron microscopy, transmission electron microscopy, ultraviolet–visible spectroscopy and thermogravimetric analysis techniques were used for the characterization of the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 44 publications
(92 reference statements)
1
31
0
Order By: Relevance
“…Thus, the electrical conductivity can be controlled and tuned by any interaction that can change the quantity and mobility of charge carriers. Consequently, the electrical conductivity can precisely be tuned by changing both the type and level of oxidation as well as the types and amount of filler components [ 23 , 24 , 40 , 41 , 42 , 43 , 44 ]. In conducting polymer-nanocomposites, the mechanism of conductivity is described by the movement of charge carriers along with the extended π-conjugated system of polymer backbone or/and the hopping/tunnelling between fillers and polymer chains [ 23 , 43 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the electrical conductivity can be controlled and tuned by any interaction that can change the quantity and mobility of charge carriers. Consequently, the electrical conductivity can precisely be tuned by changing both the type and level of oxidation as well as the types and amount of filler components [ 23 , 24 , 40 , 41 , 42 , 43 , 44 ]. In conducting polymer-nanocomposites, the mechanism of conductivity is described by the movement of charge carriers along with the extended π-conjugated system of polymer backbone or/and the hopping/tunnelling between fillers and polymer chains [ 23 , 43 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Whereas in the air, the conductivity of the sensor started to increase and became saturated ( Figure 9 ). The % sensing response of PPy and PPy/CeO 2 based sensors was evaluated by employing the formula where σ i and ∆σ correspond to the initial DC electrical conductivity and change in the conductivity of sensor-pellets in the ammonia vapor for 200 s, respectively [ 21 , 40 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This slightly expanded the diameter of nanotubes, which were close to the diameter of pristine MWCNT-OH, and this might explain that a longer reaction time was required to enhance the interaction between P3HT and MWCNT-OH. Such ununiform P3HT wrapped over the MWCNT-OH sidewall could be attributed to a low electronic interaction between the lone pair of sulphur ions in P3HT and the π-bond from MWCNT-OH [63], whereas nanocomposites that were prepared at 72-and 96-hour reaction times showed that the nanotubes were dispersed homogenously with less entanglement and more aligned tubes. This might be due to sufficient time for the P3HT to swell, make an interaction and wrap the MWCNT-OH sidewalls.…”
Section: High-resolution Transmission Electron Microscopy Analysismentioning
confidence: 99%